Towards an assessment instrument for suffering in patients with psychiatric conditions: assessing cognitive validity - Verhofstadt, Monica (BJPsych Open, 2019)
BACKGROUND: Unbearable suffering is a key criterion in legally granting patients' euthanasia requests in Belgium yet a generally accepted definition of unbearable suffering remains elusive. The ability to understand and assess unbearable suffering is essential, particularly in patients with psychiatric conditions, as the underlying causes of these conditions are not always apparent. To enable research into when and why suffering experiences incite patients with psychiatric conditions to request euthanasia, and to help explore preventive and curative perspectives, the development of an assessment instrument is needed. AIMS: To improve the cognitive validity of a large initial item pool used to assess the nature and extent of suffering in patients with psychiatric conditions. METHOD: Cognitive validity was established via two rounds of cognitive interviews with patients with psychiatric conditions with (n = 9) and without (n = 5) euthanasia requests. RESULTS: During the first round of cognitive interviews, a variety of issues relating to content, form and language were reported and aspects that were missing were identified. During the second round, the items that had been amended were perceived as sufficiently easily to understand, sensitive to delicate nuances, comprehensive and easy to answer accurately. Neither research topic nor method were perceived as emotionally strenuous, but instead as positive, relevant, comforting and valuable. CONCLUSIONS: This research resulted in an item pool that covers the concept of suffering more adequately and comprehensively. Further research endeavours should examine potential differences in suffering experiences over time and in patients with psychiatric conditions with and without euthanasia requests. The appreciation patients demonstrated regarding their ability to speak extensively and openly about their suffering and wish to die further supports the need to allow patients to speak freely and honestly during consultations. DECLARATION OF INTERESTS: None.